Avaliação de diferentes configurações de hidrólise enzimática e fermentação utilizando bagaço de cana-de-açúcar para a produção de etanol 2G - Silva, Gislene Mota da (2015)
Sugarcane bagasse (SCB) is a by-product generated after sugarcane milling in the process of manufacture of sugar and/or ethanol. In this study, pretreated SCB was used in different configurations of enzymatic hydrolysis and fermentation. The objective was obtaining the greatest amounts of fermentable sugars in the enzymatic conversion and then converted them to ethanol. SCB was hydrothermally pretreated (1:10 (w/v), solid-liquid ratio) under the conditions 170 °C/15 min, 195°C/10 min, and 195 °C/60 min at 200 rpm. The delignification step of the hydrothermal pretreated SCB was carried out with 0.02 and 0.5% NaOH solution at 1:10 (w/v). Pretreated and untreated samples of SCB were chemical and morphologically characterized. Enzymatic hydrolysis and fermentation assays were carried out in PSSF (pre-saccharification prior to simultaneous saccharification and fermentation) process. In the best condition, (10% pretreated SCB at 195 °C/10 min) it was obtained 57.4% of ethanol yield. SSF (simultaneous saccharification and fermentation) experiments were performed in Erlenmeyer flasks at 250 rpm and at 37 °C using commercial Saccharomyces cerevisiae during 72 h. In the first assay, it was evaluated the effect of initial buffered medium and non-buffered medium for hydrothermal pretreated SCBs. In the best result, it was obtained 53.8% of enzymatic conversion and an ethanol titer of 17.1 g/L (SCB pretreated at 195 °C/10 min in buffered medium). In the next assays, it was evaluated the effect of solid loading (10 and 15%) on delignified and non-delignified SCB using an enzyme loading of 20 FPU/g pretreated SCB. In these assays were obtained ethanol yields of 53.8 (17.1 g/L) and 60.0% (28.4 g/L) for 10 and 15% of SCB, respectively. These results showed that the increased in solid loading favored obtaining higher ethanol yield. Assays in SHF configuration (separate hydrolysis and fermentation) using delignified and non-delignified samples of SCB achieve ethanol concentration of 39.9 g/L and ethanol yield was 84% with 15% loading at 72 h. Other experiments were carried out in 10% SCB/15 FPU/g SCB loading, 10% SCB/30 FPU/g SCB loading, 15% SCB/15 FPU/g SCB loading and 15% SCB/30 FPU/g SCB loading employing the thermotolerant yeasts Kluyveromyces marxianus IMB3 and Saccharomyces cerevisiae D5A to ethanol production from hydrothermal pretreated SCB. The results showed enzymatic conversion was 64.3% and maximum ethanol concentration of 29.2 g/L using 15% of SCB at 72 h. D5A yeast showed ethanol yield was 76.2% and the maximum ethanol concentration of 42.6 g/L at 120 h using 15% of solid load and 30 FPU/g SCB of enzyme load. Overall, all evaluated conditions showing satisfactory results in obtaining ethanol from hydrothermal pretreated SCB. However, high concentration of substrate loading favored SHF process to operate separately enzymatic hydrolysis and fermentation. This configuration achieved high ethanol yields in the conditions assessed in this work.